Persoanele care nu pot fi supuse răspunderii contravenționale în Republica Moldova [Articol] - Şova, Liuba (Tipografia Artpoligraf, 2018)
According to the principle of equality before the law, all persons who have committed contraventions are equal before the law and public authorities and are subject to contravention without distinction as to race, nationality, language, religion, sex, political affiliation, wealth, social origin or any other situation. This principle is not absolute, that is, in certain cases also allows some derogations, which are expressly and exhaustively regulated by law. In accordance with the provisions of the Supreme Law, other laws and/or international treaties to which the Republic of Moldova is a party, certain categories of persons may benefit from special conditions of contravention or from the guarantee not to be subject to prosecution and contravention. Diplomatic representatives of foreign states or other persons who, in accordance with the international treaties to which the Republic of Moldova is a party or in accordance with the laws of the Republic of Moldova, can not be subject to contravention liability under the jurisdiction of the contraventional jurisdiction of the Republic of Moldova or for which it is removed contravention. All persons who can not be subjected to contravention, according to the general rule in par. (3) Art. 4 CC, conventionally, may be grouped into categories, of which: 1. the diplomatic representatives of foreign states or other persons assimilated in immunities with diplomatic representativeswho do not fall under the national contravention jurisdiction in accordance with the international treaties to which the Republic of Moldova is a party or in accordance with the laws of the Republic of Moldova; 2. persons who, in accordance with the laws of the Republic of Moldova, do not fall under the jurisdiction of the contraventional jurisdiction of the Republic of Moldova, and 3. persons for whom the contraventional liability is removed. Asylum seekers (who may only be foreigners or stateless persons) are exempted from contravention: a) only if it protects the Republic of Moldova under one of the forms of asylum and, b) only for offenses committed for illegal entry or stay on the territory of the Republic of Moldova. From the category of persons, in which, in certain circumstances, the contravention is removed, the holders of the travel documents issued by the foreign authorities residing in the localities on the left bank of the Dniester (Transnistria) are also included.
PERSONS WHO CAN NOT BE LIABLE CONTRAVENTION IN THE REPUBLIC OF MOLDOVA
Keywords: răspunderea contravențională